2015
DOI: 10.1080/09540121.2015.1045406
|View full text |Cite
|
Sign up to set email alerts
|

HIV-positive African-American women’s perspectives on engaging communities in the response to HIV/AIDS in Washington, D.C.

Abstract: The number of African American women infected with HIV in Washington, D.C. is growing at an alarming rate. However, the perspectives of these women on engaging communities in the response to HIV/AIDS have been lacking in the literature. To fill this gap, in-depth interviews with 18 HIV-positive African American women living in D.C. were conducted and analyzed using thematic network analysis. Three key themes emerged from these interview: (1) the importance of the church in building HIV/AIDS community competenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…HIV-related stigma refers to the, "prejudice, discounting, discrediting and discrimination that are directed at people perceived as having HIV." 11 Negative experiences with HIV-related stigma are well-documented among African-American women living with HIV, [12][13][14][15] and these experiences have been associated with isolation, 16 decreased psychological functioning, 17 and other symptoms of depression. [18][19][20] Moreover, many African-American women experience other forms of stigma on account of race, gender and socioeconomic status .…”
Section: Introductionmentioning
confidence: 99%
“…HIV-related stigma refers to the, "prejudice, discounting, discrediting and discrimination that are directed at people perceived as having HIV." 11 Negative experiences with HIV-related stigma are well-documented among African-American women living with HIV, [12][13][14][15] and these experiences have been associated with isolation, 16 decreased psychological functioning, 17 and other symptoms of depression. [18][19][20] Moreover, many African-American women experience other forms of stigma on account of race, gender and socioeconomic status .…”
Section: Introductionmentioning
confidence: 99%
“…The publication dates range from 2014 to 2019. Among the 11 studies, four of them focused on women living with HIV (Melton, 2014; O'Daniel, 2016; Sanicki & Mannell, 2015; Watkins‐Hayes, 2019). Of these four, two of them included populations other than Black women (McLane‐Davison, 2014; Watkins‐Hayes, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Relatedly, Black women living with HIV also describe supportive relationships and shared experiences amongst Black women as a mechanism of empowerment that influences their decision to participate in activism (Sanicki & Mannell, 2015). Researchers conducted a series of semi‐structured interviews to explore 18 HIV‐positive Black women's perspectives on community engagement in response to HIV/AIDS in Washington D.C. (Sanicki & Mannell, 2015). Using thematic network analysis, they found that social bonds they developed in a weekly support group with other Black women were an integral component of their participation in advocacy and activism.…”
Section: Resultsmentioning
confidence: 99%
“…Women living with HIV have stated that identifying what is important in their life, which can vary depending on their circumstance, motivates them to adhere to treatment. 4 , 5 Thus, interventions that incorporate goal setting help participants focus on what is important to achieve a sense of balance between the difficulties associated with managing HIV and comorbidities and other life responsibilities, such as caring for children. 6 Project THANKS takes an individualistic approach by allowing the women to set goals that will ultimately motivate them to adhere to treatment.…”
Section: The Need For Project Thanks For African American Wlwhmentioning
confidence: 99%
“…Research has suggested that African American WLWH may be at a particularly high risk for psychological distress compared to African American men and white women and men. 5 Project THANKS addresses the concerns of HIV-positive African American women who are dealing with multiple chronic conditions (ie, diabetes, hypertension, or heart disease), mental health disorders, and substance use disorder and have unique contextual needs. African American women as a whole are at an increased risk for poverty, are more likely to be unmarried and under or uninsured than whites, and often place their health care needs behind other family members, that is, spouses, children, and grandchildren.…”
Section: How Does Your Research Contribute To the Field?mentioning
confidence: 99%